2011
DOI: 10.1007/s10551-011-0919-5
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent is Business Responding to Climate Change? Evidence from a Global Wine Producer

Abstract: Most studies on climate change response have examined reductions in greenhouse gas (GHG) emissions. Yet these studies do not take into account ecosystem services constraints and biophysical disruptions wrought by climate change that may require broader types of response. By studying a firm in the wine industry and using a research approach not constrained by structured methodologies or biased toward GHG emissions, the findings suggest that both ''inside out'' and ''outside in'' actions are taken in response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 64 publications
(82 reference statements)
0
90
1
1
Order By: Relevance
“…The literature increasingly seeks to unpack the detailed drivers that motivate economic agents to adapt or prevent them from doing so (Averchenkova et al, 2016;Hertin, Berkhout, Gann, & Barlow, 2003;Agrawala et al, 2011;Galbreath, 2011;Berkhout, 2012;Linnenluecke et al, 2013;Pauw & Pegels, 2013;Pauw, 2015). While the primary motive of firms may be to keep down costs, minimize disruptions or increase sales, the way the relevant decisions are taken is influenced by a range of additional factors.…”
Section: The Adaptation Behavior Of Firmsmentioning
confidence: 99%
“…The literature increasingly seeks to unpack the detailed drivers that motivate economic agents to adapt or prevent them from doing so (Averchenkova et al, 2016;Hertin, Berkhout, Gann, & Barlow, 2003;Agrawala et al, 2011;Galbreath, 2011;Berkhout, 2012;Linnenluecke et al, 2013;Pauw & Pegels, 2013;Pauw, 2015). While the primary motive of firms may be to keep down costs, minimize disruptions or increase sales, the way the relevant decisions are taken is influenced by a range of additional factors.…”
Section: The Adaptation Behavior Of Firmsmentioning
confidence: 99%
“…The ABV has recently been used as a theoretical lens in the business sustainability literature-for example, the ABV was leveraged to explain corporate social responsibility and performance (Zhao et al, 2016), climate change adaptation (Pinske and Gasbarro, 2016;Galbreath, 2011), and green information system practices adoption (Hedman and Henningsson, 2016). Pinske and Gasbarro (2016) study on the oil and gas industry indicates that different attention channels (selective, situated, and structural) lead to different climate change adaptation strategies.…”
Section: Linking Supply Chain Uncertainty To Environmental Managementmentioning
confidence: 99%
“…Galbreath (2011) (Lim-Camacho et al, 2015). This research also found that policy and regulatory frameworks can impede adaptation opportunities in seafood supply chains, highlighting a need for governments to engage in adaptation planning (Lim-Camacho et al, 2015).…”
Section: Responses To Emerging Climate Risks In Australian Agri-food mentioning
confidence: 72%
“…In Australia, responses to climate change have been studied in the sheep/beef, grains, horticulture, and peanut industries , Marshall et al, 2014, Milne et al, 2008, WIDCORP, 2009, though the wine and seafood sectors have received the most attention , Galbreath, 2011, Galbreath, 2014 most actively pursuing climate adaptations are those that have directly experienced an increase in climate impacts, such as drought or extreme weather events , Galbreath, 2011, Lim-Camacho et al, 2015, Marshall et al, 2014, Park et al, 2012.…”
Section: Responses To Emerging Climate Risks In Australian Agri-food mentioning
confidence: 99%
See 1 more Smart Citation